Clinical profile and outcome of multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19 infection: a single-center observational study from South India - Brundavanam Venkata Krishna Sai; Hema Kumar; Thirunavukkarasu Arun Babu; Raghuvamsi Chaitra; Diptirekha Satapathy; Vinoth Kumar Kalidoss (SpringerOpen, 2023)
Abstract Background Multisystem inflammatory syndrome in children (MIS-C) is a post-infectious sequelae of acute COVID-19 infection affecting children. This study was done over a period of 12 months from December 2020 to November 2021 to describe the clinical presentation, laboratory abnormalities, and outcome of children with MIS-C. Methods Seventy-eight children below 12 years of age who satisfied the WHO diagnostic criteria for MIS-C were included in the study. Clinical parameters were recorded at admission. Relevant laboratory investigations, radiological studies, and outcome were documented. Results The most commonly affected age group was 6-12 years with a female predominance. COVID RTPCR was negative in all patients. Most cases presented 2-6 weeks after the onset of acute COVID-19 infection. Lethargy, poor feeding, vomiting, abdominal pain, loose stools, cough, and cold are common symptoms of MIS-C syndrome in children and the common signs were rash, conjunctival congestion, hypotension, tachycardia, tachypnea, and hypoxemia. Gastrointestinal system was the commonly affected followed by the hepatic, renal, and cardiovascular systems. Coronary artery abnormalities were seen in 20% of cases. IVIg was the mainstay of therapy used in 95% of patients. Mortality was 1.3%. Cases responded well to IVIg and steroids. Conclusion Overall, the short-term outcome was favorable with low mortality in our study cohort. One-fifth of children had coronary artery abnormalities during acute phase underscoring the need for long-term follow-up.